Repurposing of blended fabric waste for sustainable cement-based composite: Mechanical and microstructural performance. (2nd January 2023) - Tran, Nghia P.; Gunasekara, Chamila; Law, David W.; Houshyar, Shadi; Setunge, Sujeeva
Highlights: Hydrophilic fabric fibres refine the pore structure of cementitious matrices. Hybrid hydrophobic and hydrophilic fibres counterbalance the pore-refining effects. Fabric waste fibres suppress the crack propagation and mitigate the quantity of cracks. Hybrid fabric fibres significantly reduces the shrinkage of cementitious composites. Blended fabric waste fibres can improve strength properties of cement-based materials. Abstract: In this study, the strength properties, shrinkage and microstructures of mortar incorporating blended fabric fibres were characterised via X-ray micro CT and nanoindentation. Three different hybrid recycled fabric fibres, namely Kevlar/Nomex, Kevlar/Nylon and Nomex/Nylon fibres were investigated at three different blend ratios (2:1, 1:1, and 1:2). The fibre content was maintained at 0.3 % for all mixes. The findings indicated that the optimum blend ratio for hybrid fabric fibres is 1:1. At this optimum fibre blend ratio, an enhancement by 2.7 %, 4.8 % and 5.9 % in compressive strength, together with 9.8 %, 12 % and 13.4 % in flexural strength of mortar are recorded, corresponding to the inclusion of hybrid Nomex/Nylon, Kevlar/Nomex and Kevlar/Nylon fibres respectively. Kevlar/Nomex fibres display no effect in drying shrinkage mitigation, irrespective of blend ratios. In contrast, Kevlar/Nylon and Nomex/Nylon fibres result in reducing 180-day shrinkage rates by up to 13.9 % and 11 % respectively. The hybrid fabric fibres were found to refine the pore network, especially the highly hydrophilic Kevlar/Nomex fibres. Also, an increase in curing days from 7 to 90 days densifies the microstructure near the fibre-matrix interface due to the growth of hydration products (LD/HD CSH and CH). These research findings can open the pathway for utilising textile waste in landfill as reinforcing members for cementitious matrices toward sustainable building and construction.